1993
DOI: 10.1017/s1049023x00040243
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Agents Utilized in Urban/Rural Prehospital Care

Abstract: Introduction:Objectives of this study were to determine the number of prehospital emergency patients who were given advanced life support (ALS) drugs and to compare utilization rates for ALS drugs in urban and rural environments. Certified ALS emergency medical technicians (Arizona) have 29 therapeutic agents authorized for prehospital administration. These agents may be administered only under direction of a medical control authority or by following standing orders.Methods:A retrospective review was made of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…1 More typically it may be used to develop a database useful in medical billing 2 or for capture of data for later study of patient cohorts, disease classification, medical events, practices, treatments or outcomes. [3][4][5][6][7][8][9] The approach has also been used to study environmental and occupational health issues 10 or cancer prevalence and risk factors. 11 Scannable case report forms and automatic reading, evaluation and transfer of information to database are also being introduced into pharmaceutical trials.…”
Section: Discussionmentioning
confidence: 99%
“…1 More typically it may be used to develop a database useful in medical billing 2 or for capture of data for later study of patient cohorts, disease classification, medical events, practices, treatments or outcomes. [3][4][5][6][7][8][9] The approach has also been used to study environmental and occupational health issues 10 or cancer prevalence and risk factors. 11 Scannable case report forms and automatic reading, evaluation and transfer of information to database are also being introduced into pharmaceutical trials.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with an altered level of consciousness (ALOC) frequently are encountered in the prehospital setting and commonly are treated with a variety of pharmacologic agents. 1 However, there has been little research to evaluate the impact of prehospital medical care on patient outcome. It has been suggested that most patients with an ALOC should not be treated in the field.…”
Section: Introductionmentioning
confidence: 99%